PROFESIONALISME GURU-GURU MADRASAH IBTIDAIYAH MUHAMMADIYAH CEPER - Djumali, Djumali (Jurnal Pendidikan Ilmu Sosial, 2014)
The aim of the research is to know the influence of teacher education level towards teachers’ professionalism in Madrasah Ibtidaiyah Muhammadiyah Ceper Klaten. The kind of research is descriptive quantitative with expost facto approach by using research subject 63 MIM teachers. From 63 teachers were taken samples 53 by Simple Random Sampling. Technique of data collection is by using Questionaire, Documentation, and Interview directly. To know whether there is influece or not, by using regression linier analysis with SPSS program for windows versi 11.0.The research result showed that Regression similarity Y = 84,450 + (-1,270) X, where regression coeficient is -1,270 dengan signifikan 0,262 stated that much bigger than 0,05 it means Ho is rejected (X can not predict Y). The level of teachers’ education influenced teachers’ professionalism is 2,4 % while 97,6 % is influenced by other factors.